The effect of different administrations of testosterone therapy on adverse prostate events: A Bayesian network meta-analysis - Zeng, Bin; Qiu, Shi; Xiong, Xingyu; Su, Xingyang; Zhang, Zilong; Wei, Qiang; Yang, Lu (Frontiers in Endocrinology, 2022)
Background Hypogonadism has become a major cause endangering men’s health and quality of life all over the world. Testosterone Therapy (TT) is a widely accepted treatment for relieving hypogonadal symptoms. However, the effect of different administrations of TT on prostate safety is still unclear. Methods We did a thorough search of PubMed, Embase and Cochrane Library to identify eligible studies up to January 2022. Randomized controlled trials (RCTs) and Cohort studies evaluating the impacts of using different formulations of TT on prostate parameters were included. Changes of prostate-specific antigen (PSA) level and prostate cancer (Pca) cases were used as the primary outcomes. Quality of individual studies was estimated by RoB2 (Cochrane tool for assessing the risk of bias in randomized trials) and the Newcastle-Ottawa scale (Tool for assessing non-RCTs). Certainty of evidence for each study was evaluated according to the evidence assessment criteria of the Oxford Evidence-based Medicine Center. Random-effect network meta-analysis(NMA)was performed based on the Bayesian model. Results Thirty-five studies (30 RCTs and 5 Cohort studies) with 7,740 participants were included. TT administration led to fewer Pca patients (RR=0.62, 95%CI [0.39,0.99], I2=0%), while little decreasing in PSA level (MD=-0.05, 95%CI [-0.08, -0.02], I2=0%). The NMA revealed that compared with other formulations, the intramuscular injection was the most likely to rank first in decreasing Pca cases. The TT also resulted in more biopsy cases (RR=2.38, 95%CI [1.01,5.60], I2=0%). As for NMA, intramuscular injection also performed relatively better in fewer prostate biopsy cases compared with transdermal group. Conclusion TT does not lead to abnormal PSA changes and increased risk of Pca in patients with hypogonadism or low testosterone level. Compared with other preparations of TT, intramuscular injection proved better in minimizing Pca cases and was more likely to result in fewer prostate biopsy cases.